Pengaruh Lingkungan Belajar Terhadap Sikap Pasukan Gegana Korbrimob Polri Dalam Pelatihan KBRN Tactical - NDOLUANAK, YOFRAN HENGKI; Rahayu, Wardani; Rahmawati, Yuli (Jurnal Evaluasi Pendidikan, 2023)
ABSTRACT Attitude is an important element in supporting training behavior. This research aims to determine whether there is an influence of the learning environment on the attitude of the Pasukan Gegana Korbrimob Polri in Tactical KBRN training. Classroom environment was measured using an adaptation of the What is Happening in This Class? (WIHIC) and student attitudes were measured using the participant Attitude Scale towards KBRN Tactical training based on indicators developed in the Test of Science Associated Attitudes (TOSRA). The correlation test results show that there is a significant positive relationship between the learning environment and participants' attitudes towards KBRN Tactical training (with a t table value of 4.215 and a significance value of 0.000. This means that the better the participants' perception of the learning environment, the more positive the participants' attitude towards KBRN Tactical training. In addition, the regression model shows that the learning environment makes an effective contribution of 15.39% to participants' attitudes towards KBRN Tactical training (R2 = 0.153). The research results show that the learning environment has a significant influence on participants' attitudes towards KBRN Tactical training, although not a large one. This is because there are other variables that influence participants' attitudes towards KBRN Tactical training apart from the learning environment, such as: achievement, mentor factors, peers, and other factors. Keywords: Learning Environment, Attitudes towards KBRN Tactical Training, Pasukan Gegana Korbrimob Polri